Cross linked plantain starch-urea as a polymer in matrix tablets of ambroxol hydrochloride - Adenike Okunlola; Adenike Temitayo Adedeji (University of Huddersfield Press, 2021)
Plantain (Musa paradisiaca) starch, prepared as crosslinked starch-urea (CSU), was utilized in the formulation of matrix tablets of ambroxol hydrochloride. CSU was synthesized by gelatinization of plantain starch in urea, crosslinked with calcium chloride. Native starch and CSU were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), chemical and material properties. Ambroxol hydrochloride tablets were prepared with CSU, 1:1 blend of CSU and Hydroxyl propyl methylcellulose (HPMC K15M) and HPMC K15M alone at 20, 30 and 40%w/w. The 32 factorial design was used to optimize tablets using polymer type (X1) and polymer concentration (X2) as independent variables, crushing strength-friability ratio (CSFR) and time for 80% drug release (t80) as responses. The SEM revealed changes in the ovoid granules of native starch to larger, irregular granules of CSU. The XRD spectra revealed a more crystalline CSU with higher swelling and better flow. Polymer type had more influence on CSFR and t80. The optimized batch containing CSU at 40 %w/w exhibited the highest values of CSFR and drug release. Experimental responses of the optimised batch had close proximity with the predicted value. Cross-linked plantain starch-urea polymer was found suitable as a polymer in matrix tablets of ambroxol hydrochloride.